2018
DOI: 10.12691/jfnr-6-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Production and Evaluation of Some Bakery Products Containing Ginger Powder

Abstract: The aim of the current study is to investigate the effect of adding ginger powder (0, 3, 6 and 9%) in formulation of antioxidant-enriched bakery products (e.g. bread and rusk) possessed good physico-chemical and sensorial properties. The rheological properties of doughs were evaluated using dynamic rheological measurements. Physical properties, total phenolic and total flavonoid content, antioxidant activity and sensory analysis (hedonic test) of the supplemented bread were determined. The highest phenolic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
3
1
0
Order By: Relevance
“…The highest value (0.485 mg GAE/g DW) was recorded in 6% ginger powder bread and minimum value showed in 0% (0.143 mg GAE/g DW) ginger powder bread. Similar results reported by Almasodi (2018) and Konrade & Klava, (2017) whereby TPC of bread was increased by the addition of ginger flour.…”
Section: Texture Analysissupporting
confidence: 89%
“…The highest value (0.485 mg GAE/g DW) was recorded in 6% ginger powder bread and minimum value showed in 0% (0.143 mg GAE/g DW) ginger powder bread. Similar results reported by Almasodi (2018) and Konrade & Klava, (2017) whereby TPC of bread was increased by the addition of ginger flour.…”
Section: Texture Analysissupporting
confidence: 89%
“…Another study also came up with similar findings over the functional, physicochemical, and sensory properties of bread fortified with ginger powder but with a different optimized level of ginger powder (1%) than the previous study [75]. Moreover, Almasodi [76] studied the addition of ginger powder in bread as well as in rusk. They concluded that the incorporation of up to 3% and 6% of ginger powder resulted in satisfactory hedonic and textural properties for bread and rusk, respectively.…”
Section: Bakery Productssupporting
confidence: 58%
“…This is similar to a report where high carbohydrate results were reported by Yusuf et al [55] and Giwa and Abiodun [56]. Almasodi [57] reported a similar trend for ginger powder bakery products.…”
Section: Proximate Composition Of Cookies Produced From Plantain Brea...supporting
confidence: 92%